2002
DOI: 10.1007/s00120-001-0151-5
|View full text |Cite
|
Sign up to set email alerts
|

α1-Rezeptorenblockade zur Therapie des BPH-Syndroms Richtige Dosierung für optimale Wirkung

Abstract: Four alpha 1-adrenoceptor antagonists are currently available for the medical treatment of lower urinary tract symptoms suggestive of benign prostatic obstruction in Germany: alfuzosin, doxazosin, tamsulosin, and terazosin. Indirect comparison based on randomized, placebo-controlled trials as well as several direct comparative studies have shown equal efficacy of all four drugs on urinary flow and symptom relief if suggested dosing regimens are applied. A dosing regimen below this recommendation should be rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It was found that niguldipine is a potent antagonist for α 1 -AR with a 100-fold selectivity increase for α 1a -AR versus the other α 1 -AR subtypes. Several modifications yielded compound (13) [pK i 9.63 (α 1a ), 7.87 (α 1b ) and 7.18 (α 1d )] with preserved potency and selectivity for α 1a -AR but attenuated calcium channel activity. One significant drawback of compound (13), however, is its poor oral bioavailability in rats (5%), which may be due to the oxidative metabolic conversion of the dihydropyridine moiety into a pyridine [8,29] (Fig.…”
Section: Piperidinesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that niguldipine is a potent antagonist for α 1 -AR with a 100-fold selectivity increase for α 1a -AR versus the other α 1 -AR subtypes. Several modifications yielded compound (13) [pK i 9.63 (α 1a ), 7.87 (α 1b ) and 7.18 (α 1d )] with preserved potency and selectivity for α 1a -AR but attenuated calcium channel activity. One significant drawback of compound (13), however, is its poor oral bioavailability in rats (5%), which may be due to the oxidative metabolic conversion of the dihydropyridine moiety into a pyridine [8,29] (Fig.…”
Section: Piperidinesmentioning
confidence: 99%
“…(1)). The α 1 -AR antagonists act on the dynamic component of bladder outlet obstruction, presumably by affecting the contraction of prostate and urethral smooth muscle produced by sympathetic nerve stimulation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%